Molecular dynamics simulations of pressure-broadened symmetric-top gas spectra. Application to CH3F-Ar and CH3F-He mixtures. (February 2022) - Ngo, Ngoc Hoa; Le, Minh Thu; Tran, Ha; Hartmann, Jean-Michel
Highlights: Requantized classical molecular dynamics simulations (rCMDS) were developed to compute Ar- and He-broadened CH3 F spectra. Line broadenings deduced from the simulated spectra are in good agreement with available measured values. Speed dependence effect on the simulated spectra is detected and comparable with the unique experimental data available. Line-mixing effect at high pressure in parallel bands of CH3 F is correctly predicted by rCMDS. Abstract: We present a new approach, based on requantized classical molecular dynamics simulations (rCMDS), to calculate pressure-broadened absorption spectra of symmetric-top molecules. We test it in the cases of CH3 F-He and CH3 F-Ar gas mixtures at room temperature for which predictions are made, without use of any adjusted parameter, based on input inter-molecular potentials from the literature. The results show that the Lorentz pressure-broadenings, deduced from fits of the computed spectra, are in good agreement with available measured values. Furthermore, the predicted effects of line-mixing at high pressure are also very consistent with observations. In addition, the study of the influence of the speed dependence of the pressure-broadening coefficient is promising but needs to be confirmed, since based on only one experimental result available. This opens renewed perspectives for predictions of symmetric-top molecules line shapes beyond the Voigt profile. Graphical abstract: Image, graphical abstract